Perseverance in mathematical reasoning of climber students solving linear equations in one variable - Ade Kumalasari; Rohati Rohati; Sri Winarni; Marlina Marlina; Annisa Nur Rasyid (Jurnal Elemen, 2026)
Research on mathematical reasoning has increasingly recognized perseverance as more than "not giving up"; it requires maintaining coherent reasoning when facing obstacles. However, micro-level analysis linking perseverance episodes to Adversity Quotient (AQ) dimensions remains limited, particularly in linear equation-in-one-variable contexts. The study used a descriptive qualitative approach, a single-case qualitative study that examined one climber-type student (selected via ARP questionnaire from 32 eighth graders) solving Linear Equation on Linear Variable (LEOV) tasks. Data included observations, semi-structured interviews, and written work, analyzed using Miles and Huberman's framework with source triangulation. The results show that Climber (AA) students illustrate strong Perseverance in Mathematical Reasoning (PiMR) through three integrated behaviors: (1) exploring multiple solution strategies and verifying results (Control–Endurance); (2) reflecting on errors and adapting approaches (Ownership–Reach); and (3) maintaining goal focus while revising strategies (Endurance–Control). These findings imply that mathematics instruction should systematically scaffold productive struggle, validation practices, and self-regulation to develop reasoning-specific perseverance, not merely task persistence.